2012
DOI: 10.5755/j01.em.17.4.2988
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Optimal Capital Structure in Private–public Partnership

Abstract: This paper presents the main guidelines for the formation of optimal capital structure in a publicprivate partnership (P3). The relevance of guidelines determines the growing number of investment projects carried out by various publicprivate hybrids, which, due to unique conditions of every project, usually cope with such problems as the formation of optimal capital structure and sharing of risk between shareholders. Due to this reasons, the purpose of the paper is to form a procedural model enabling to optimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Sharma et al (2010) presented a structured approach to determine the debt-equity investment between public and private sectors in PPP projects, which took into account financial factors alone. Jasiukevičius and Vasiliauskaitė (2012) formed a procedural model to evaluate the requirements for private sector's involvement in the delivery of public services, which is rather practical and focuses more on 'how' than 'why'. Albalate et al (2013) found that risk associated with cost recovery and relative cost of labour are key factors explaining the extent of private involvement.…”
Section: Private Involvement In Pppsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sharma et al (2010) presented a structured approach to determine the debt-equity investment between public and private sectors in PPP projects, which took into account financial factors alone. Jasiukevičius and Vasiliauskaitė (2012) formed a procedural model to evaluate the requirements for private sector's involvement in the delivery of public services, which is rather practical and focuses more on 'how' than 'why'. Albalate et al (2013) found that risk associated with cost recovery and relative cost of labour are key factors explaining the extent of private involvement.…”
Section: Private Involvement In Pppsmentioning
confidence: 99%
“…The formation of the private involvement in an urban rail PPP project is important to project success, as it may arise possible problems related with the role of each party and apportionment of risks, liabilities and rewards between partners (Jasiukevičius and Vasiliauskaitė, 2012). However, very few information was disclosed in the PPP literature yet.…”
Section: Five-stage Systematic Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…In China, subnational governments particularly value this meaning, especially the share of initial investment by the private sector. Second, it also denotes a more comprehensive concept including responsibilities, obligations and risks undertaken, as well as resources and skills committed to a project by the private sector, following Jasiukevičius and Vasiliauskaitė (2012).…”
Section: Knowledge Gapmentioning
confidence: 99%
“…by systemising various literature byJasiukevičius and Vasiliauskaitė (2012),Ke et al (2010b),Sharma et al (2010),Zhang (2005),Zhang and Chen (2013).…”
mentioning
confidence: 99%